Management Of Tourism Village Governance In The New Normal Era - Ariel Sabella Siva Shan; Syaiful Ade Septemuryantoro (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The New Normal era that emerged as a result of the COVID-19 pandemic presents new challenges in the management and administration of tourist villages. Tourist villages are destinations that are very vulnerable to changes in tourist behavior and government regulations. Therefore, this research seeks to understand the management of tourism village governance in the New Normal era. This research uses a qualitative approach, collecting data through in-depth interviews, field observations, and document analysis related to tourist villages. Respondents interviewed included tourist village managers, local communities and tourists. The collected data was analyzed using the content analysis method. Research findings reveal that management of tourist villages in the New Normal era faces several significant challenges. The COVID-19 pandemic has forced tourist village managers to adapt their business models, which include implementing strict health protocols and adapting tourism services to meet New Normal requirements. In addition, the active involvement of local communities in decision making and promotion of tourist villages has become an important factor in maintaining the sustainability of these destinations. This research underlines the importance of adaptation and innovation in tourism village governance in the New Normal era. Tourism village managers must collaborate with government institutions, local communities and other stakeholders to overcome existing challenges. Apart from that, prioritizing increasing awareness of health and hygiene protocols is important in facing New Normal conditions. By doing this, tourist villages can continue to operate safely and sustainably, while providing meaningful tourism experiences to their visitors.